Community structure and systematic study of Helminth parasites of freshwater snails of the Chittagong University Campus (Bangladesh Journal of Zoology, 2016)
In all, 13 parasite taxa - eight cercariae, three nematodes, one rhabdocoel and one aspidogastrean - were recorded from 205 out of the 642 snails autopsied. Of the carcariae, xiphidiocercous was the most diversified (five taxa), followed by the echinostome (two) and the furcocercous (one). Infection by the nematodes, though rather poor in diversity, was much higher (23.99%) than that (12.15%) by the developmental stages of Trematoda. The rhabdocoel and the aspidogastrean were minor infestors having 1.56% and 2.80% prevalence, respectively. Bellamya bengalensis was the most abundant host, had the highest parasite diversity (12 taxa) and also the highest prevalence of infection (51.59%). Though the second highest abundant host, Paludomus blanfordiana had the least parasite diversity (only an oxyurid nematode) and a very low prevalence (2.04%) as well. Brotia costula, the big strong snail harboured two taxa (a carcaria and a nematode), and also had a low prevalence (8.65%). The amphibious Pila globosa, though least abundant among the four hosts, had moderately high parasite diversity (four carcariae and two nematodes) and prevalence (40.26%).Bangladesh J. Zool. 44(1): 9-30, 2016